(untitled) (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The aim of the article is to explain how the Italian response capacities for the safeguarding of cultural heritage at risk of disaster has been enhanced over the past twenty-five years and how it has contributed to raising the awareness of this issue at international level. Approach/methodology. For this purpose, the main steps made in the last decades by Italy in including the protection of cultural heritage among other emergency issues are described below. In fact, Italy has made many efforts in the past decades to improve the emergency management of cultural heritage, paying particular attention to preparedness, prevention and response actions. Since the end of the past century, dedicated training courses have been organized at all levels as well as local, national and international exercises with specific scenarios dedicated to the protection of cultural heritage at risk of disaster in order to test specific procedures needed to ensure this type of response. In the meantime, the drafting of standard operating procedures specifically addressing the protection of vulnerable cultural heritage emerged as a result of a keen collaboration between the Italian Ministry of Culture (Italian acronym MiC) and the National Civil Protection Department (Italian acronym DPC). Findings. In this process of constant evolution of operational and technical capacities aimed at reducing the risk of cultural heritage disasters, the combination of past experience and acquired competences of Italy, France, Spain, Turkey, ICCROM and Fondazione Villa Montesca has prompted the launch of the PROCULTHER project, co-funded by the Directorate-General for European Civil Protection and Humanitarian Aid Operations (DG-ECHO). Value. The project aims to support and complement the efforts made by the European Union to strengthen cooperation between the EU Member States and Participating States in this field. In this sense, by pooling together European civil protection capacities and capabilities and providing for common standards enabling certified and well-equipped teams to work interchangeably when a disaster strikes, the Union Civil Protection Mechanism (UCPM), is an essential and effective system aimed at allowing a stronger and more coherent collective response. Under this framework, the project is promoting, for the first time, the development of a common European methodology, tools and capacities in order to include the protection of cultural heritage in the disaster risk management cycle and to ensure structured collaboration among cultural heritage and civil protection stakeholders at local, national and European level.